2014
DOI: 10.1257/aer.104.9.2830
|View full text |Cite
|
Sign up to set email alerts
|

Mortgage Modification and Strategic Behavior: Evidence from a Legal Settlement with Countrywide

Abstract: We investigate whether homeowners respond strategically to news of mortgage modification programs by defaulting on their mortgages. We exploit plausibly exogenous variation in modification policy induced by U.S. state government lawsuits against Countrywide Financial Corporation, which agreed to offer modifications to seriously delinquent borrowers with mortgages throughout the country. Using a difference-indifference framework, we find that Countrywide's relative delinquency rate increased more than ten perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(107 citation statements)
references
References 35 publications
4
95
3
Order By: Relevance
“…), and empirical evidence on whether, how, and how much asymmetric information actually affects market outcomes is finally catching up to theory and practice. Examples include Adams et al (2009) and Dobbie & Skiba (2013) on subprime auto and payday loans, several papers on mortgage securitization (e.g., Keys et al 2010, Bubb & Kaufman 2014, and a growing literature on strategic default by mortgagors (e.g., Mayer et al 2014).…”
Section: How To Explain the Facts? Theories And Theory Testingmentioning
confidence: 99%
“…), and empirical evidence on whether, how, and how much asymmetric information actually affects market outcomes is finally catching up to theory and practice. Examples include Adams et al (2009) and Dobbie & Skiba (2013) on subprime auto and payday loans, several papers on mortgage securitization (e.g., Keys et al 2010, Bubb & Kaufman 2014, and a growing literature on strategic default by mortgagors (e.g., Mayer et al 2014).…”
Section: How To Explain the Facts? Theories And Theory Testingmentioning
confidence: 99%
“…We employ a difference‐in‐differences model along the lines of that used by Mayer et al . () in their analysis of the countrywide settlement. We use a linear probability model (LPM) with interaction terms.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Mayer et al . () show that in response to a court mandated change in mortgage contract terms, borrowers who otherwise would have been unlikely to default stopped making payments to be eligible for more attractive loan terms.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, any evidence that delinquencies would increase substantially due to aggressive modifications was thin. In a paper that has been cited as evidence of mortgage modifications encouraging borrowers to become delinquent, Mayer, Morrison, Piskorski, and Gupta (2011) found that even after a major settlement was announced in which delinquent Countrywide borrowers would unilaterally be offered aggressive loan modifications, the proportion of borrowers going from being current to being 60 days delinquent rose only from 4.8% to 5.43%, an increase of 13%. This scale of moral hazard effect would seem to be one that might be easily compensated for by the benefits of reduced foreclosures.…”
Section: Immergluck 224mentioning
confidence: 99%